Participation in the European Public Prosecutor’s Office Member States’ Autonomous Decision or an Obligation? - Békés Ádám (HUNGARIAN YEARBOOK OF INTERNATIONAL LAW AND EUROPEAN LAW, 2020)
The aim of the present study is to examine recent developments concerning the European Public Prosecutor’s Office (EPPO), focusing on the conflict between the EU and the Member States not participating in the enhanced cooperation setting up the Prosecutor’s Office. To provide an overall picture about EPPO’s future operational relations, the study first presents the EPPO’s future cooperation with other EU bodies and draws some critical conclusions. Based on these reflections, the study aims to discuss the EU’s alleged intention and strategy to cope with and solve the problem of non-participating Member States, assessing the probable role of the Prosecutor’s Office and other related EU bodies, institutions and legal measures in this struggle, while also considering recent declarations of the leaders of EU institutions.